Predicting progression of in situ carcinoma in the era of precision genomics - Cheng, Monica; Hanna, Nasser H.; Davidson, Darrell D.; Gunderman, Richard B. (Journal of Thoracic Disease; Vol 11, No 6 (June 29, 2019): Journal of Thoracic Disease, 2019)
Cancer control depends on early detection, a discipline formalized in the 1950s by widespread use of the Papanicolaou test for detecting pre-invasive squamous epithelial neoplasia of the uterine cervix (1-3). Studies growing out of that public health initiative have revealed a long latency between the earliest cellular abnormalities and invasive cancer. Pre-invasive or intraepithelial neoplasia arises in predisposed benign tissue, often influenced by metaplasia or inflammation (4,5). These precursor lesions can be reliably diagnosed by the microscopic appearance, but the biological behavior of these lesions is difficult to predict by histology alone. In situ carcinoma of the cervix or breast has only a 50% probability of eventually becoming invasive cancer (1-3).